Study on improving the method of cutting carcass of Jinhua Pig - TAO Zhi-lun; FU Yan; HE Ying-jun; WANG Yan-li; YAN Han-guang (浙江大学学报. 农业与生命科学版, 2005)
Multiple correlation and regression analysis were conducted based on the data concerning cutting carcass of Jinhua Pig. Formulas for estimating lean percentage from various carcass traits were derived. The result showed that the lean percentage estimated from skin and fat rate attained a high degree of accuracy. The differences between real value and of lean percentage and the estimated value were 0.578-0.865 (P>0.05), indicating the fitness and practicalility of the formulas.